School Literacy Movement in the Industrial Revolution Era 4.0 in Building Speed Reading Skills - Walipah, Eva; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2020)
The low reading interest in Indonesia is a reason why the School Literacy Movement (GLS) is urgent to face of the industrial revolution 4.0 which is an all-digital era. Read quickly ability give effect in competition at the global level so GLS is needed in order to increasing of studentâ€™s reading speed ability. This research is aimed to get knows the effect of GLS on students’ reading speed at SDN Karapyak 1. This research was conducted in semester 1 started from July to December academic year 2018/2019. Research approval is a descriptive qualitative discussion. The sample of the research is 74 students of grade IV. Data collection by KPM test (speed reading per minute). Based on the first KPM test, only 4 students (5.4%) gets grades above the KPM standard, after treats by the GLS program in the second test, around 54 students (73%) gets grades above the KPM standard, as allocated 67, 6%. So that the School Literacy Movement Program can improve reading skills of fourth grade students in elementary schools Karapyak 1